(untitled) (ENTHYMEMA, 2013)
Ricœur evokes continuously the extraordinary resources offered by fiction to catch the subtle variants between the time of conscious and the chronological time, and finds the limits of history: compared to historical narrative, – writes Ricœur - fiction narrative is richer in information on time, because of its powers of composition.